Volume-controlled inverse ratio ventilation improves safe apnea time in obese patients during the induction of general anesthesia: a randomized controlled trial - Zhang, Yonghai; Li, Bin; Xu, Chang; Wu, Yan; Ma, Ling; Yang, Fan; Ma, Hanxiang; Ni, Xinli (Frontiers in Medicine, 2025)
BackgroundInverse ratio ventilation theoretically increases oxygenation in obese patients. However, it is unknown whether the use of inverse ratio ventilation prolongs the safe apnea time during the induction of anesthesia. The primary objective of our study was to compare the safe apnea time between obese surgical patients receiving inverse ratio ventilation and conventional ratio ventilation during the induction of anesthesia.MethodsThis study is a prospective, randomized controlled trial. Forty obese patients who underwent elective operation under general anesthesia with endotracheal intubation were randomly allocated into the conventional ratio ventilation (CRV) group (n = 20) and inverse ratio ventilation (IRV) group (n = 20). After the patients were preoxygenated through a face mask for 3 min, anesthesia induction was performed. When the patients lost consciousness and spontaneous breathing disappeared, non-invasive positive pressure ventilation was performed for 5 min, and the inspiratory-to-expiratory (I:E) ratio was set as 1:2 in the CRV group and 2:1 in the IRV group. Heart rate, systolic blood pressure, diastolic blood pressure, and pulse oxygen saturation were recorded at four time points: (i) before pre-oxygenation (T0), (ii) pre-oxygenation for 3 min (T1), (iii) non-invasive positive pressure ventilation for 3 min (T2), and (iv) non-invasive positive pressure ventilation for 5 min (T3). Arterial blood was collected at T0, T1, and T3 for arterial blood gas analysis, and arterial oxygen partial pressure and carbon dioxide partial pressure were recorded. The patient’s expiratory oxygen fraction at T1, T2, and T3 were recorded. Peak airway pressure, plateau pressure and mean airway pressure were record at T2 and T3. The safe apnea time was recorded in both groups.ResultsForty patients completed the study. Baseline parameters were comparable between the two groups. Safe apnea time was significantly longer (210.40 ± 47.47 vs. 153.80 ± 41.54 s, mean difference [95% CI], 56.55 [28.00–85.10], p = 0.0003) and the expired O2 fraction was higher (87.60 ± 2.39 vs. 91.60 ± 1.79, mean difference [95% CI], 4.00 [2.65–5.35], p < 0.0001) at T3 in the IRV group compared to the CRV group.ConclusionVolume-controlled inverse ratio ventilation at an I:E ratio of 2:1, compared to conventional ratio ventilation, provided a longer safe apnea time and higher expired O2 fraction in obese patients during the induction of anesthesia.